(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
School nurses are healthcare professionals that are educated in medicine and work in both the school and healthcare industries. Their goal is to provide a healthy environment for teachers and students in the school setting [1-3]. School nurses have a crucial role in enhancing the health and overall well-being of children and teenagers. They do this by offering health promotion, health counseling, referring to other sources of assistance, giving active treatment, education, family support, coordinating care, and collaborating with many agencies [1,4–6]. School nurses possess a diverse array of tasks and responsibilities that include three fundamental components of school health: 1) health literacy, 2) medical care, and 3) health promotion [7–9]. The three domains of school nursing are mutually supportive in their aim to create a health-promoting environment in schools, but they vary in their methods and tactics to accomplish this objective. The goal of health literacy is to empower students and instructors to locate, comprehend, assess, and use health information for making health-related choices, with the objective of preserving or enhancing health and quality of life [10,11].